EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN MEDIA KARTU SOAL PADA SUB MATERI IKATAN KOVALEN KELAS X MIA DI SMA ISLAM HARUNIYAH PONTIANAK - Zulfadhli Abdillah (Universitas Muhammadiyah Pontianak, 2018)
This study is motivated by the low learning outcomes in the Sub-covalent Bond class of tenth-grade students, SMA Islam Haruniyah Pontianak. This problem is due to the lack of students' understanding of the concept of Covalent Bonds. Therefore, a proper learning model is required to improve students’ understanding of Covalent Bond concepts based on the characteristics of both learning materials and students. This study aimed to investigate the differences in the student learning outcomes and the effectiveness of the question card-based on TGT learning in the Sub-covalent Bonding material. Using the pre-experimental method of one-group pretest-posttest design, the tenth-grade students of Math and Science Class of SMS Islam Haruniyah Pontianak participated in this study. The data collection tools used were learning outcomes tests, observation sheets, and interview sheets. The results of data analysis revealed that the average pretest score was 36 and the posttest was 62.94. In addition, the t-test statistical analysis indicated a significance value of 0.00 (0.00 <0.05) which meanth that there were differences in student learning outcomes between before and after the question card-based TGT learning model implemented. The gain value was 0.42. In other words, the question card-based on TGT learning model is effective in improving the student learning outcomes with good category. Keywords: Covalent Bond, Question Card, Team Games Tournament (TGT)